2003
DOI: 10.1002/rra.704
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblage response to recent mitigation of a channelized warmwater stream

Abstract: Various designs of low-head dams are used to rehabilitate streams or forestall upstream channel incision after channelization. We report on the efficacy of using notched sills and grade control structures (GCS) to restore the fish assemblage in Luxapallila Creek, Mississippi. We tested the null hypotheses that habitat variables and species richness, evenness, and assemblage structure would not differ among: (1) a channelized segment with no modifications; (2) a channelized segment mitigated by the installation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Gillette et al (2005) and Poulet (2007) also found the similar influence of low-head dams on fish assemblages in impoundment areas. However, Dodd et al (2003) and Raborn and Schramm (2003) revealed that, despite of the significant variation in local habitat, fish assemblage structures in the impoundment areas were not significantly altered by low-head dams. Gillette et al (2005) explained these different patterns by the differing spatial scales used in these studies.…”
Section: Influences Of Low-head Dams On Fish Assemblagesmentioning
confidence: 88%
See 2 more Smart Citations
“…Gillette et al (2005) and Poulet (2007) also found the similar influence of low-head dams on fish assemblages in impoundment areas. However, Dodd et al (2003) and Raborn and Schramm (2003) revealed that, despite of the significant variation in local habitat, fish assemblage structures in the impoundment areas were not significantly altered by low-head dams. Gillette et al (2005) explained these different patterns by the differing spatial scales used in these studies.…”
Section: Influences Of Low-head Dams On Fish Assemblagesmentioning
confidence: 88%
“…Whereas, Dodd et al (2003) observed that fish species richness peaked just below low-head dams, which is due to that these dams block fish movement upstream. Although Raborn and Schramm (2003) and Dodd et al (2003) showed no difference in fish assemblage structures between dammed and free-flowing stream segments, this difference in fish assemblages was observed by Gillette et al (2005) and Poulet (2007). In addition, Lessard and Hayes (2003) discovered that, by increasing water temperature downstream, the surface release of lowhead dams caused the decrease in densities of coldwater fish species and the increase in overall fish species richness within the segments immediately downstream of dams.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These scoured channels have lost much, if not all, of their original habitat; for example, many of these streams are devoid of riffle-pool sequences, except at very low baseflow. Prime fish habitat has been shown to be adversely affected by bed degradation in other studies (Shields et al 1994;Raborn and Schramm 2003). Due to extreme downcutting, many channels have lost lateral connectivity with their former floodplains, except in the most extreme flow discharge events.…”
Section: Introductionmentioning
confidence: 95%
“…Extensive channel erosion has also caused dramatically increased sediment loads. The altered flow regimes, loss of habitat, loss of connectivity, and high sediment loads caused by channel incision has led to decreased biodiversity (Hansen, 1971;Shields et al, 1994;Bravard et al, 1997;Cooper et al, 1997;Shields et al, 1998;Raborn and Schramm 2003). Bunn & Arthington (2002) noted that in highly altered environments, invasive species may find it easier to out-compete native species in the new, altered environment.…”
Section: Introductionmentioning
confidence: 99%